2006
DOI: 10.1080/01443610600963770
|View full text |Cite
|
Sign up to set email alerts
|

Haematological profile of healthy pregnant women in Ibadan, South-western Nigeria

Abstract: There is a dearth of information on the reference values for haematological indices particularly according to the relevant trimesters of pregnant women in Nigeria. The objective of this study was to provide reference values for Nigerian pregnant women. The study took place at the Adeoyo Maternity Hospital and the University College Hospital, both in Ibadan. This descriptive study was carried out over a period of 8 months. Subjects were apparently healthy pregnant women that satisfied the inclusion and exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
25
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 12 publications
14
25
3
Order By: Relevance
“…Still in agreement with our finding was a study by Akingbola et al [10], from Ibadan South-west Nigeria, that found a significantly higher platelet counts in their non-pregnant women compared to the pregnant women. Their results of Hb and WBC in pregnancy were also consistent with ours.…”
Section: Discussionsupporting
confidence: 81%
“…Still in agreement with our finding was a study by Akingbola et al [10], from Ibadan South-west Nigeria, that found a significantly higher platelet counts in their non-pregnant women compared to the pregnant women. Their results of Hb and WBC in pregnancy were also consistent with ours.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were demonsterated by Akinbami et al, [5], who found that a progressive decline in Hb concentration from the first to the third trimester. These findings corroborate those of a similar study undertaken in Ibadan, south-western Nigeria, by Akingbola et al [24] in 2006, which reported exactly the same pattern. The progressive decline in Hb concentration from the first to third trimester may be due to an increased demand for iron as pregnancy progresses [5].…”
Section: Discussionsupporting
confidence: 83%
“…The increase observed in WBC count from the first to third trimester in this study is consistent with the findings of Akinbami et al, [5], Onwukeme and Uguru [11], and Akingbola et al, [24]. The increase is primarily due to an increase in neutrophils and may represent a response to stress due to redistribution of the WBCs between the marginal and circulating pools [5,33].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, massive and fatal obstetric haemorrhages occur in 3 to 5% of deliveries and in 30 to 50 per 100,000 deliveries, transfusion of blood products is required [4]. Hemorrhage during labour, delivery, pregnancy and postpartum accounts for 34% of maternal deaths in West Africa [5] and the overall outcome is more severe against a backdrop of severe anaemia in pregnancy and possibly a poor marrow reserve [6]. Quite a lot of these deaths in developing nations are preventable, as demonstrated by an audit of five hospitals in Senegal-48% of deaths were rated avoidable and 25% were considered probably avoidable.…”
Section: Introductionmentioning
confidence: 99%